Analisis Spasial Bencana Longsor Bukit Telogolele Kabupaten Banjarnegara Menggunakan Data Foto Udara UAV - Ruli Andaru; Purnama Budi Santosa (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
Spatial data is a very important role in emergency command and disaster management, before, during or post disasters. When a disaster occurs, the currently geospatial information is very needed: where the center of the disaster, the area affected, the volumetric of the landslide, what facilities are damaged, and determine the location of temporary shelters. This study examines and analyze the landslide in Banjarnegara 2014 before and after the landslide using Peta Rupa Bumi Indonesia (RBI) and the UAV Aerial Photos (Unmanned Aerial Vehicle). Data before the landslide obtained from RBI, while data after landslide obtained by performing aerial photography using fixed-wing UAV in December 2014 and August 2015. These aerial photos processing with photogrammetry to produce digital orthophoto and DEM (Digital Elevation Model). Orthophoto and DEM data is used to perform geospatial analysis in both 2D and 3D. 3D analysis obtained from the extraction of DEM elevation map data values appearance of the earth (RBI) and the UAV Aerial Photo. Analysis was conducted on the four components: contouring, terrain profile/cross section, slope/gradient, and volumetric (cut and fill). Readiness management of geospatial data and information is necessary to minimize losses and speed up the process of rehabilitation and reconstruction in the areas affected by the disaster. With this spatial analysis, the estimated of volume of landslides, mapping the facility affected, and the manufacture of the soil profile (high landslide, landslide affected area) can be performed quickly and accurately.